1996
DOI: 10.1016/0014-5793(96)00807-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative regulation of a sterol biosynthetic gene (ERG3) in the post‐squalene portion of the yeast ergosterol pathway

Abstract: Regulation of sterol biosynthesis in the terminal portion of the pathway represents an efficient mechanism by which the cell can control the production of sterol without disturbing the production of other essential mevaionate pathway products. We demonstrate that mutations affecting early and late steps in sterol homeostasis modulate the expression of the ERG3 gene: a late step in sterol biosynthesis in yeast. Expression of ERG3 is increased in response to a mutation in the major isoform of HMG CoA reductase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 16 publications
6
70
0
Order By: Relevance
“…In contrast, changes in the sterol composition of TM DGA1 ϩ and TM LRO1 ϩ cannot be attributed to substrate specificities of (missing) SE synthases but rather to a feedback regulation to the sterol biosynthetic pathway. This view is in line with data reported by ArthingtonSkaggs et al (39) showing that lack of Are1p or Are2p downregulated Erg3p. This down-regulation may be the reason for the accumulation of ergosta-7-enol and ergosta-7,22-dienol (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, changes in the sterol composition of TM DGA1 ϩ and TM LRO1 ϩ cannot be attributed to substrate specificities of (missing) SE synthases but rather to a feedback regulation to the sterol biosynthetic pathway. This view is in line with data reported by ArthingtonSkaggs et al (39) showing that lack of Are1p or Are2p downregulated Erg3p. This down-regulation may be the reason for the accumulation of ergosta-7-enol and ergosta-7,22-dienol (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…TM DGA1 ϩ and TM LRO1 ϩ , which lacked sterol esterification, accumulated ergosta-7,22-dienol and ergosta-7-enol at the expense of other sterol precursors. This effect may be explained by down-regulation of Erg3p as reported previously by Arthington-Skaggs et al (39) and will be discussed FIGURE 2. Activities of neutral lipid-synthesizing enzymes in vitro.…”
Section: Fatty Acid Analysis Of the Se Fractions Revealed That In Tm supporting
confidence: 65%
See 1 more Smart Citation
“…The relatively low ASAT activity in yeast might be the reason that WS/DGAT was unable to restore steryl ester synthesis in S. cerevisiae H1246. Another reason might be a lower intracellular concentration of sterols in the mutant, since it has been shown that down-regulation of sterol biosynthesis occurred in mutants defective in ARE1 and ARE2 (3,37). However, the sterol content in S. cerevisiae H1246 was not determined in this study.…”
Section: Discussionmentioning
confidence: 70%
“…This may be because ergosterol itself was able to exert feedback regulation at different steps of the pathway. Indeed, the expression of ERG3, for example, was shown to be dependent on the endogenous ergosterol level [45]. A proposed hypothesis to explain the deregulation of the pathway could be that SUT1 overexpression might result in the upregulation of HMG2 which is normally repressed in aerobiosis and is less sensitive to retro-inhibition by ergosterol than HMG1 [46].…”
Section: Discussionmentioning
confidence: 99%